A core‐top study of dissolution effect on B/Ca in Globigerinoides sacculifer from the tropical Atlantic: Potential bias for paleo‐reconstruction of seawater carbonate chemistry. (29th April 2013) - Coadic, R.; Bassinot, F.; Dissard, D.; Douville, E.; Greaves, M.; Michel, E.
Abstract: [1] It has been recently shown that B/Ca in planktonic foraminiferal calcite can be used as a proxy for seawater pH. Based on the study of surface sediments (multi‐cores) retrieved along a depth transect on the Sierra Leone Rise (Eastern Equatorial Atlantic), we document the decrease of B/Ca and Mg/Ca of Globigerinoides sacculifer shells with increasing water depth and dissolution. This effect of dissolution on B/Ca may potentially represent a severe bias for paleo‐pH reconstructions using this species. Samples of G. sacculifer were analyzed independently at two laboratories for B/Ca and Mg/Ca. Both sets of results show a systematic decrease of B/Ca and Mg/Ca along the depth transect, with an overall loss of 14 µmol/mol ( 15%) for B/Ca and of 0.7 mmol/mol ( 21%) for Mg/Ca between the shallowest (2640 m) and the deepest (4950 m) sites. Because of this dissolution effect, surface water pH reconstructed from B/Ca of G. sacculifer decreases by 0.11 units between the shallowest site and the deepest site, a magnitude similar to the expected glacial/interglacial surface water pH changes. Key Points: Planktonic foraminifera as geochemical tracer Seawater paleo‐pH reconstruction B/Ca of planktonic foraminifera modified by dissolution